Epidemiology of subclinical mastitis in family size dairy farms in hatay region - Yaşar Ergün; Özkan Aslantaş; Zafer Cantekin (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the prevalance of the subclinical mastitis in family size (3-10 cows for each farm) dairy farms in Hatay region. For this purpose, California Mastitis Test (CMT) was performed to 160 cows (640 quarters) in different localities belong to 11 towns in Hatay. A total of 262 milk samples from 115 (71.9 %) mastitic cows were investigated for aerobic pathogenic microorganism. From this 262 milk samples, 231 aerobic microorganisms were isolated and identified in 200 milk samples. Isolated and identified microorganism were also tested for antibiotic susceptibility against to 12 different antibiotics. The number and rate of isolated microorganisms were 98 (42.4 %) Coagulase Negative Staphylococcus (CNS), 58 (25.1 %) S. aureus, 26 (11.2 %) S. uberis, 15 (% 6.5), S.agalactiae, 8 (3.5 %) S. dysgalactiae, 5 (2.2 %) Bacillus spp., 4 (1.7 %) Candida spp., 6 (2.6 %) Micrococcus spp., 4 (1.7 %) P. auriginosa, 2 (0.9 %) S. faecalis, 4 (2.2 %) £ coli. The most effective antibiotics were Danofloxacine, Sulbactam+Ampicilline, Enrofloxacin, Amoxicillin+Clavulanic acid and Cefoperazone. As a result, the prevalance of subclinical mastitis was determined high in family size dairy farms in Hatay. Antibiotic resistancy was determined against some common used antibiotics.